Rhizopus oligosporus-Assisted Valorization of Coconut Endosperm Waste by Black Soldier Fly Larvae for Simultaneous Protein and Lipid to Biodiesel Production - Chung Yiin Wong; Kunlanan Kiatkittipong; Worapon Kiatkittipong; Jun Wei Lim; Man Kee Lam; Ta Yeong Wu; Pau Loke Show; Hanita Daud; Pei Sean Goh; Mina Sakuragi; Elfis Elfis (Processes, 2021)
Coconut endosperm waste (CEW) was treated by Rhizopus oligosporus via in situ and ex situ fermentations together with bioconversion into valuable black soldier fly larval biomass. The ex situ fermentation could overall enrich the nutritional compositions of CEW by hydrolyzing its complex organic polymers and exuding assimilable nutrients to enhance the black soldier fly larvae (BSFL) growth. Nevertheless, the larval gut bacteria were competing with Rhizopus oligosporus in in situ fermentation, derailing the hydrolysis processes and larval growth. Accordingly, the highest growth rates achieved were around 0.095 g/day, as opposed to only 0.065 g/day whilst using 0.5 wt% of Rhizopus oligosporus to perform ex situ and in situ fermentations, respectively. These were also underpinned by the greater amount of total CEW consumed when employing ex situ fermentation, with comparable metabolic costs to feeding on in situ-fermented CEW. The mature BSFL were subsequently harvested and the amounts of protein and lipid produced were assessed in terms of their feasibility for biodiesel production. While the statistical analyses showed that the larval protein yields derived from both fermentation modes were insignificant, the BSFL could attain higher lipid and protein productivities upon feeding with ex situ- rather than in situ-fermented CEW mediums. Better yet, the larval biodiesel quality measured in terms of the fatty acid methyl ester composition were not varied significantly by Rhizopus oligosporus through the fermentation process. Thereby, the presence of 1.0 wt% Rhizopus oligosporus was considered optimum to perform ex situ fermentation, giving rise to the acceptable growth of BSFL loaded with the highest lipid yield and productivity for producing biodiesel and protein simultaneously.
Keywords: Insect Utilization and Effects; Protein Hydrolysis and Bioactive Peptides; Aquaculture Nutrition and Growth